Asymmetric Wars: A Study of the Concept, Characteristics, Features, and Causes - Abousi , Assist prof Dr. Haider Zayer Abousi; Al-Ghazali, Ali Nayef (The International and Political Journal, 2023)
Asymmetric wars is becoming one of the most important subjects that had been studied by the specialist of strategic studies. as well as other political studies, because this war it's have different range than the regular war by its themes and causes. The standard war was a subject for studies and research for a long time and for many reasons one of which that these standards wars was drain too much resources and manpower and because Disastrous results hit the community's and the mankind and cause backwards for humanity. Although there are many common features. between the different types of wars, asymmetric wars are characterized by characteristics and features that differ to a large extent from the characteristics and features that characterized conventional wars, in addition to the fact that there are multiple other reasons behind the escalation of this type of war or Threats, including economic, political, religious and cultural reasons. Likewise, those types of wars have their own tools or means, through which they are threatened or used against the other hostile party that disagrees with the threatened party, with reference to a fundamental and important point, which is the inequality of the warring parties, as the asymmetric war may be carried out by a weaker party than the other. In terms of physical (hard) force, the threat may come from units or other non-international actors such as terrorist organizations or some extremist groups, or even from individuals. All this made the study of asymmetric threats or wars a matter of interest to researchers and specialists, because of the dangers that these wars and threats pose to the international community and human security, and negatively affect the economic and cultural development of the international community.